Study on exhaled volatile organic compounds identifying cognitive fatigue induced by N-back task in healthy young adults - Xiaoyu Zhang; Xiaoyan Dong; Qiang Huang; Zhe Liu; Qin Wang (Ecotoxicology and Environmental Safety)
Cognitive fatigue in specific occupations may present a risk to personal safety. The study aimed to explore the characteristic volatile organic compounds (VOCs) in exhaled breath in response to cognitive fatigue, to provide a scientific basis for the non-invasive exhaled breath diagnostic techniques for cognitive fatigue assessing. Thirty healthy young adults were recruited and assigned to complete two 1.5-hour cognitive fatigue-inducing trials of the N-back task and one control trial of low emotion film watching of the same duration time. The Chalder Fatigue Scale was employed to assess the cognitive fatigue of the subjects before and after the induction and film watching. Exhaled VOCs were collected and detected using a Bio-VOC sampler and Thermal Desorption Gas Chromatography-Mass Spectroscopy method. The differences in exhaled VOCs between the pre- and post-induction and film watching was evaluated using either the paired t-test or the Wilcoxon signed-rank test. It was found that the scale scores of the task group (n = 50) significantly increased after the induction, whereas no such findings were observed in the control group (n = 10), indicating that the cognitive fatigue state of the task group was effectively induced through the performance of the N-back task. A total of 15 VOCs were identified in the exhaled breath samples of the task group. And only the level of isoprene changed significantly from 339.77 ± 162.21 μg/m³ to 604.18 ± 230.75 μg/m³ with the induction of cognitive fatigue. In contrast, the change of isoprene in the control group was not statistically significant. The study demonstrated that after inducing cognitive fatigue by N-back task in healthy young subjects, isoprene levels in exhaled breath increased significantly. It suggests that isoprene could be considered a characteristic volatile organic compound in exhaled breath associated with cognitive fatigue.